SIMS ANALYSIS OF U-PB ISOTOPES IN MONAZITE: MATRIX EFFECTS - Zhu X.K.; O'Nions R.K.; Gibb A.J. (My University, 1998)
The calibration of U-Pb and Th-Pb ratios in Th-U-rich minerals measured by SIMS usually assumes that there are no matrix effects arising from the compositional difference between standard and sample. Matrix effects have been observed during attempts to calibrate U-Pb ratios of monazite using a SIMS energy-filtering technique on the ISOLAB-120 ion probe. Thus matrix effects cannot be assumed to be insignificant a priori for SIMS U-Pb or Th-Pb chronometry, and need to be investigated more thoroughly. A general approach to the investigation of matrix effects for SIMS U-Pb and Th-Pb analysis is proposed.
Keywords: MATRIX EFFECTS; SIMS CHRONOMETRY; MONAZITE; U-PB ISOTOPES; GEOCHRONOLOGY